Analisis Pengembangan Karir Dan Budaya Organisasi, Terhadap Komitmen Organisasi Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT Jasa Raharja Cabang Utama Jawa Timur - Anindya Ikasari; Eka Askafi; Imam Baehaki (Universitas Islam Kadiri, 2022)
The Influence Of Career Development And Organizational Culture, On Organizational Commitment With Job Satisfaction As Intervening Variable In PT Jasa Raharja Main Branch East Java. This study uses quantitative research with a descriptive verification approach. The number of samples is 65 respondents. Analysis of the data used is by using SPSS. This type of research is quantitative research by distributing questionnaires through google form to employee at PT Jasa Raharja Main Branch East Java. This study uses multiple linear regression. The results show that (1) Career development has a significant positive effect on Job Satisfaction, (2) Organizational Culture has a significant positive effect on Job Satisfaction, (3) Career development has no significant effect on Organizational Commitment, (4) Organizational Culture has no significant positive effect on Organizational Commitment, (5) Job Satisfaction has a significant positive effect on Organizational Commitment, (6) Career development has an indirect effect on Organizational Commitment, (7) Organizational Culture has no direct effect on organizational commitment and job satisfaction is able to mediate Organizational Culture with organizational commitment .